NiWO4 powders prepared via polymeric precursor method for application as ceramic luminescent pigments - Lima, Naiara A. (2020)
NiWO4 was prepared using the polymeric precursor method and studied in terms of physical and chemical properties to verify its stability for industrial applications as pigments. The characterization was accomplished using thermal analyses, X-ray diffraction (XRD), scanning electron microscopy (SEM), photoluminescence (PL) and UV-Vis spectroscopies, colorimetric coordinates, and Raman spectra. Increasing the temperature, successive exothermic reactions were observed and they are related with thermal decomposition of the organic compound. The stability was reached at similar to 700 degrees C. The material is verified to become completely free of second phase at similar to 800 degrees C. The end NiWO4 powders showed an intense charge transfer (CT)-related tail centered in the ultraviolet region, resulting in a yellow product. In addition, the powders exhibited broad excitation band and broad deep blue-green emission band, which were enhanced with increasing powders' crystallinity.